Damage evolution of 3D woven carbon/epoxy composites under tension-tension fatigue loading based on synchrotron radiation computed tomography (SRCT). (January 2021) - Guo, Licheng; Huang, Jinzhao; Zhang, Li; Sun, Xinyang
Highlights: A novel method based on SRCT for the fatigue damage of 3D woven composites. The relationship between the stiffness degradation and temperature variation. The damage mechanisms at every fatigue stages for 3D woven carbon/epoxy composites. The effects of the yarns' undulation and twist on the fatigue damage. Abstract: A method combining mechanical testing, infrared thermography (IRT) and synchrotron radiation computed tomography (SRCT) is proposed for the damage evolution of 3D woven carbon/epoxy composites under tension-tension (T-T) fatigue loading. To study the relationship between the damage evolution and the stiffness degradation, fatigue tests of six specimens are carried out to different stages before detection by SRCT and optical microscope. The detected results have revealed how cracks initiate, distribute and develop with increasing fatigue cycles. Particularly, the effects of fiber yarn undulation and twist caused during the manufacturing process are discussed.